Pulse oximetry for the prediction of acute mountain sickness: A systematic review - Johnathan S. L. Goves; Kelsey E. Joyce; Sophie Broughton; Julian Greig; Kimberly Ashdown; Arthur R. Bradwell; Samuel J. E. Lucas (Experimental Physiology)
Abstract Acute mountain sickness (AMS) causes serious illness for many individuals ascending to high altitude (HA), although preventable with appropriate acclimatisation. AMS is a clinical diagnosis, with symptom severity evaluated using the Lake Louise Score (LLS). Reliable methods of predicting which individuals will develop AMS have not been developed. This systematic review evaluates whether a predictive relationship exists between oxygen saturation and subsequent development of AMS. PubMed, PubMed Central, MEDLINE, Semantic Scholar, Cochrane Library, University of Birmingham Library and clinicaltrials.gov databases were systematically searched from inception to 15 June 2023. Human studies involving collection of peripheral blood oxygen saturation (SpO2) from healthy lowlanders during ascent to HA that evaluated any relationship between SpO2 and AMS severity were considered for eligibility. Risk of bias was assessed using a modified Newcastle–Ottawa Tool for cohort studies (PROPSPERO CRD42023423542). Seven of 980 total identified studies were ultimately included for data extraction. These studies evaluated SpO2 and AMS (via LLS) in 1406 individuals during ascent to HA (3952–6300 m). Risk of bias was ‘low’ for six and ‘moderate’ for one of the included studies. Ascent profiles and SpO2 measurement methodology varied widely, as did the statistical methods for AMS prediction. Decreasing oxygen saturation measured with pulse oximetry during ascent shows a positive predictive relationship for individuals who develop AMS. Studies have high heterogeneity in ascent profile and oximetry measurement protocols. Further studies with homogeneous methodology are required to enable statistical analysis for more definitive evaluation of AMS predictability by pulse oximetry.